Level Of Satisfaction Of Students With Learning Physical Education In Class Viii Students Of Smp Negeri 4 Mandau Post Pandemic Covid-19 - Muhammad Alfadil; Oki Candra (CV. AFDIFAL MAJU BERKAH, 2023)
This research is discusses the counter-terrorism strategies implemented by the New Zealand government following several terrorist attacks, including the Christchurch shooting (2019) and the Dunedin and Auckland stabbings (2021). Using Arthur Lyyke's strategy theory (2008), this study analyzes the means, ways, resources, and risk considerations inherent to effective counter-terrorism strategies. The study applies the counter-terrorism approach proposed by Jones & Libicki (2008), which divides counter-terrorism strategies into three categories: military deployment approach, police and intelligence approach, and policy approach. Through qualitative research with an analytical-descriptive approach, the study finds that the New Zealand government's counter-terrorism strategy comprises of two main approaches: the police and intelligence approach and the policy approach. The government's